Structural mechanism of DNA recognition by the p204 HIN domain. Issue 5 (22nd February 2021) - Fan, Xiaojiao; Jiang, Jiansheng; Zhao, Dan; Chen, Feng; Ma, Huan; Smith, Patrick; Unterholzner, Leonie; Xiao, Tsan Sam; Jin, Tengchuan
Abstract: The interferon gamma-inducible protein 16 (IFI16) and its murine homologous protein p204 function in non-sequence specific dsDNA sensing; however, the exact dsDNA recognition mechanisms of IFI16/p204, which harbour two HIN domains, remain unclear. In the present study, we determined crystal structures of p204 HINa and HINb domains, which are highly similar to those of other PYHIN family proteins. Moreover, we obtained the crystal structure of p204 HINab domain in complex with dsDNA and provided insights into the dsDNA binding mode. p204 HINab binds dsDNA mainly through α2 helix of HINa and HINb, and the linker between them, revealing a similar HIN:DNA binding mode. Both HINa and HINb are vital for HINab recognition of dsDNA, as confirmed by fluorescence polarization assays. Furthermore, a HINa dimerization interface was observed in structures of p204 HINa and HINab:dsDNA complex, which is involved in binding dsDNA. The linker between HINa and HINb reveals dynamic flexibility in solution and changes its direction at ∼90° angle in comparison with crystal structure of HINab:dsDNA complex. These structural information provide insights into the mechanism of DNA recognition by different HIN domains, and shed light on the unique roles of two HIN domains in activating the IFI16/p204 signaling pathway.